Adjusting for population structure in genetic association studies - Balding, David (Henry Stewart Talks, 2007)
Effect of population structure in generating spurious associations, Cause of problem is confounded by pedigree, Pre-2006 solutions: design based (TDT), genomic control, structured association, New solutions in 2006: null markers as regression covariates, principal components as regression covariates, linear mixed models using pairwise kinships